Assessing trade creation and trade diversion effects of Asean free trade area - Sharifah Azrin-Azalea, binti Wan Zawawie (Universiti Malaysia Sarawak (UNIMAS), 2014)
Over the last 22 years, intra-ASEAN trade has found to be liberalized through the formation of AFTA. This study aims to investigate whether the formation of AFTA has strengthened the intra-regional trade by empirically examine the impact of AFTA on intra-ASEAN trade because the arguments still exist whether the formation of AFTA has strengthened the intraregional trade. In respond to the critics on many past studies that used only aggregate data that provides no information on the nature of intra-trade activities at the commodity level, this study employs the extended gravity model at disaggregated level using the two-digit Standard International Trade Classification (SITC) Revision 2 for all commodities. Based on Hausman specification test, the random effect model was selected for the panel analysis of AFTA member exports for the period 1980 to 2012. Of 66 sets of regressions that I run, the coefficients of AFTA were statistically significant in 55 cases. Income level, population, transportation costs and AFTA effect have found to be significant with intra-ASEAN trade. The results show that trade creation exists for SITC0 (live animals for food), SITC 2 (crude materials), SITC 3 (mineral fuels), SITC 4 (animal and vegetable oils) and SITC 9 (other commodities). This indicates that AFTA has been a successful in promoting intra-ASEAN trade. However, ASEAN needs to improve its policies especially targeting on growth and development as majority of the commodities being traded fell under electronics and automotive categories. On the other hands, the AFTA member countries need to explore other sectors that are available to them such as agricultural business to overcome problems with food security and hunger problems.